DIY John Curtin: Uncertain futures for heritage and citizenship in the era of digital friends and foes - Hartley, John; Lucy, Niall; Briggs, Robert (Sage Publications, 2013)
This article introduces some of the problems confronting the popularization of national, civic and cultural heritage in the era of complex digital systems and social networks. Taking contemporary knowledge of John Curtin (Australia’s wartime PM) as its point of departure, the discussion explores some of the broader transformations of the conditions of citizenship, communication, heritage and knowledge production, and considers their implications for civic education and the uses of archives. In a novel thought experiment, the article explores some ways in which the figure of ‘John Curtin’ may be repurposed and reinvented for a new kind of DIY civic education based on user-led innovation.